2018
DOI: 10.1007/s10661-018-6891-0
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover change and its impacts on protected areas in Mengla County, Xishuangbanna, Southwest China

Abstract: Land use/land cover change (LUCC) in tropical areas threatens biodiversity and protected area integrity and then affects global ecosystem functions and services. In this study, the spatiotemporal patterns and processes of LUCC in Mengla County, Xishuangbanna, which is located on the northern edge of tropical Asia, were examined using a modified post-classification change detection technique based on random forest classifiers and Landsat images acquired at a 5-year time interval (e.g., 1994, 1999, 2004, 2009, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…While various works have revealed the extent of forest loss in response to Rohingya settlement, none of them have examined impact on ecosystem functions resulting from forest loss. Since natural resources such as forests provide a range of ecosystem services, clearing of forest (i.e., land use changes due to the refugee crisis) is highly detrimental to the integrity of the ecosystem and damages biodiversity (Jin & Fan, 2018; Tilman et al, 2017). In addition, forest clearance enhances carbon emission (Heiskanen, Adhikari, Piiroinen, Packalen, & Pellikka, 2019; Shi et al, 2019) and fragmentation of landcover damages biodiversity (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While various works have revealed the extent of forest loss in response to Rohingya settlement, none of them have examined impact on ecosystem functions resulting from forest loss. Since natural resources such as forests provide a range of ecosystem services, clearing of forest (i.e., land use changes due to the refugee crisis) is highly detrimental to the integrity of the ecosystem and damages biodiversity (Jin & Fan, 2018; Tilman et al, 2017). In addition, forest clearance enhances carbon emission (Heiskanen, Adhikari, Piiroinen, Packalen, & Pellikka, 2019; Shi et al, 2019) and fragmentation of landcover damages biodiversity (Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term monitoring of the spatial changes of construction lands in the Bogda area showed that tourism development influences the ecosystem and accelerates the evolution process of tourism-environment interaction. The higher land-use intensity of tourism construction influenced the landscape fragmentation, diversity, stability, primitive, and nature degree in protected areas, as suggested in previous research (Xie et al, 2012;Huong et al, 2014;Mao et al, 2014;Yuan and Fan, 2018;Li G D et al, 2020). However, tourism development might not have been the main driver of the degradation of the Bogda area ecosystem, as shown by the following two reasons.…”
Section: Discussionmentioning
confidence: 83%
“…The review also illustrated that the number of classes, landscape types, and classification algorithms has an impact on classification accuracy (Congalton & Green, 1999;Olofsson et al, 2014). For instance, Jin and Fan (Jin & Fan, 2018) obtained the highest overall accuracy of 97.90% by applying RF and Landsat images when they classified only five land cover types. In contrast, Li et al, (2017a) acquired the lowest accuracy rate of 75% when classifying 19 types of LU and LC.…”
Section: Research Developments and Challenges In Accuracy Assessmentmentioning
confidence: 96%